2012
DOI: 10.1097/scs.0b013e318240fe9b
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Morphogenetic Protein 2–Transduced Mesenchymal Stem Cells Improve Bone Regeneration in a Model of Mandible Distraction Surgery

Abstract: We demonstrated acceleration of osteogenesis in a dog model for bone distraction by using an implant of BMP-2 modified MSCs. These results are helpful for future clinical trials of mandible bone distraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…Dong and colleagues reported that complete bone healing was achieved using MSCs transduced with a recombinant adenovirus AdCbfa1a at 12 weeks after a lesion to the right radius in the front leg in rabbits [39]. In the canine model where the implant with MSCs transduced with AdBMP2/AdBMP7 was previously tested, radiographic followup showed complete healing in the treated jaw at week 6 after distraction [23]. These data indicate a marked reduction in bone healing time when genetically modified MSCs are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong and colleagues reported that complete bone healing was achieved using MSCs transduced with a recombinant adenovirus AdCbfa1a at 12 weeks after a lesion to the right radius in the front leg in rabbits [39]. In the canine model where the implant with MSCs transduced with AdBMP2/AdBMP7 was previously tested, radiographic followup showed complete healing in the treated jaw at week 6 after distraction [23]. These data indicate a marked reduction in bone healing time when genetically modified MSCs are used.…”
Section: Discussionmentioning
confidence: 99%
“…The implant was constituted by bone marrow MSCs transduced with BMP2 and embedded in DBM [23]. For the present report, the challenge was to repair a major lesion in the tibia of a sheep model.…”
Section: Introductionmentioning
confidence: 99%
“…This abnormality occurs in humans [2-8], dogs [9-40], cats [32,41-44], horses [45], cattle [46], goats [47], sheep [48] buffalo [49] and camels [50]. A review of canine cases is presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Bone morphogenetic protein 2 (BMP-2) plays an important role in regulating osteoblast differentiation and subsequent bone formation (21-23). However, TNF-α can restrain BMP-2 signaling in osteoblastic differentiation (24-26).…”
Section: Introductionmentioning
confidence: 99%